The history of the discovery of embryonic diapause in mammals - Jane C. Fenelon; Marilyn B. Renfree (2018)
The first incidence of embryonic diapause in mammals was observed in the roe deer, Capreolus capreolus, in 1854 and confirmed in the early 1900s. Since then scientists have been fascinated by this phenomenon that allows a growing embryo to become arrested for up to 11 months and then reactivate and continue development with no ill effects. The study of diapause has required unraveling basic reproductive processes we now take for granted and has spanned some of the major checkpoints of reproductive biology from the identification of the sex hormones to the hypothalamic–pituitary axis to microRNA and exosomes. This review will describe the history of diapause from its origins to the current day, including its discovery and efforts to elucidate its mechanisms. It will also attempt to highlight the people involved who were instrumental in progressing this field over the last 160 years. The most recent confirmation of mammalian diapause was in the panda in 2009 and there are still multiple mammals where it has been predicted but not yet confirmed. Furthermore, there are many questions still unanswered which ensure that embryonic diapause will continue to be a topic of research for many years to come. Note that there have recently been several extensive reviews covering the recent advances in embryonic diapause, so they will be mentioned only briefly here. For further information refer to Renfree and Shaw 2014; Fenelon et al 2014; Renfree and Fenelon 2017, and references therein.